Safety of slow‐pulsed transcranial electrical stimulation in acute spike suppression. Issue 12 (11th November 2019) - Holmes, Mark D.; Feng, Rui; Wise, Mackenzie V.; Ma, Chengxin; Ramon, Ceon; Wu, Jinsong; Luu, Phan; Hou, Jidong; Pan, Li; Tucker, Don M.
Abstract: We examined the effects of slow‐pulsed transcranial electrical stimulation (TES) in suppressing epileptiform discharges in seven adults with refractory epilepsy. An MRI‐based realistic head model was constructed for each subject and co‐registered with 256‐channel dense EEG (dEEG). Interictal spikes were localized, and TES targeted the cortical source of each subject's principal spike population. Targeted spikes were suppressed in five subject's (29/35 treatment days overall), and nontargeted spikes were suppressed in four subjects. Epileptiform activity did not worsen. This study suggests that this protocol, designed to induce long‐term depression (LTD), is safe and effective in acute suppression of interictal epileptiform discharges.